Surgical Management of Cardiac Myxoma: A 6 Years’ Experience - Elayouty, Hamdy D.; Amin, Mursi M.; Sami, Ahmed M.; Alboghdadi, Mohamed A. (Medical Science: Trends and Innovations Vol. 10, 2025)
Introduction: Atrial myxomas account for 35% to 50% of primary cardiac tumors. Myxomas are the most significant cardiac tumors, not only because of their frequency but also because the potential for total cure after surgical removal is high. The patient`s presenting symptoms may be stroke, syncope, chest pain, fever, or loss of weight. The major determinant of this cure is supposed to be the complete excision of these atrial myxomas whatever the pathological or clinical features of the tumor mass. Objectives: The aim was to evaluate the result of complete surgical excision of myxomas having divergent clinical presentations and different pathological features. Methods: The current prospective study included fourteen female and eight male patients with a mean age of 42 ± 2.3 years. Left atrial myxomas were found in 18 (82%) and right atrial ones in four (18%) cases. Frequent clinical findings included fatigue: in 16 (73%), dyspnea: in 14 (84%) and prolonged fever: in four cases (18%). Diastolic murmur at the apex was detected in eight patients but at the tricuspid area in two cases. Pansystolic murmur in two at the apex. Electrocardiography showed atrial fibrillation in three and ventricular hypertrophy in two cases. Two-dimensional trans-thoracic echocardiography diagnosed myxoma in 20 cases; the remaining two needed trans-esophageal echocardiography. Two had mitral regurgitation. Preoperative coronary angiography detected significant coronary artery disease that indicated coronary angioplasty in two cases. Twenty-two patients had open heart surgery via median sternotomy for excision of the myxomas. Two of them had mitral valve repair in the same session. A Biatrial approach was also done for patients in need of mitral valve repair. Results: Cardiopulmonary bypass time ranged between 75 and 115 minutes. Aortic cross-clamp time ranged between 45 and 60 minutes. The mean stay in the intensive care unit was 1± 0.5 days and the hospital stay was 10 ± 2.6 days. Operative findings showed that the tumors arose from the atrial septum in 19 cases, from the left atrial wall in one and from the mitral valve annulus in two cases. Dimensions of the masses ranged between 3 and 7 centimeters. Myxomas were pedunculated in 18 patients (82%) and sessile in four (18%) tumors. Pathologically, all masses were benign true neoplasms. There were no early or late hospital deaths or strokes, there were two cases of wound infection. The mean follow-up was 5.6 ± 0.5 years. Patients did not show any recurrences, new arrhythmias or septal leakage. Conclusions: Long-term follow-up after complete excision of atrial myxomas with a safety margin of surrounding atrial tissue showed no recurrences, new arrhythmias or septal leakage in spite of preoperative divergent clinical and pathological features. Median sternotomy remains the most common surgical approach for myxoma excision. However, the minimally invasive approach appears to be emerging, especially in developed countries.